Earnings management practices and the impact of institutional ownership, share moratorium and retained ownership on earnings management discretionary behaviour of the Malaysian IPO companies - Kalgo, Sani Hussaini (2015)
Initial public offering (IPO) is an extraordinary corporate event in Malaysia because apart from being a vital source of finance, it has also been extensively used in implementing government fiscal policy measures for redistribution of income, wealth creation and corporate ownership restructuring which are the cornerstones of the peaceful coexistence of its multicultural society. In the spirit of IPO‟s significance in Malaysia, this thesis examines four separate issues. First, it investigates real and accrual earnings management discretionary behaviour of Malaysian IPO firms listed on Bursa Malaysia in the period 2002-2013 in terms of nature, direction and quantum. Second, third and fourth issues relate to the impact of institutional ownership, moratorium regulation and retained ownership on IPO firm‟s earnings management (both real and accrual discretionary behavior) respectively. Applying models developed by Dechow et al. (1995) and Roychowdhury (2006) to measure IPO firm‟s accruals and real earnings management respectively, the results indicate that first, Malaysian IPO firms engage in both real and accrual discretionary behaviour around the IPO corporate event. Second, it confirms institutional shareholders‟ ability to constrain IPO firms‟ earnings management in line with international evidence. Third, the results indicate that share moratorium firms exhibit higher earnings management than non-share moratorium firms albeit statistically insignificant. This supports the Securities Commission Malaysia and Bursa Malaysia‟s policy guideline of subjecting all IPO firms to share moratorium regulations as a commitment device to reduce information asymmetry. Finally, the research document evidence of a significant negative association between retained ownership and real earnings management which is understandable given its impact on firm value. Additionally, the results provide evidence of trade-off between accrual and real earnings discretionary behaviour among Malaysian IPO firms as a result of tightening of regulations and various regulatory reforms. It reflects the importance of individual line accounting items instead of relying solely on earnings for investors‟ valuation of the IPO firms apart from considering real earnings management activities in their investment strategy. Overall, the study adds to IPO earnings management literature by providing better understanding of Malaysian IPO firms‟ reporting behavior and reinforces the need to constrain real earnings management by regulators.